The Effect of Smoking on SIRT3 and Selected Biochemical Variables in Patients with Parkinson’s Disease - Noor Abdulsatar Majeed; Mohammed Bahry Hassin (Medical Journal of Babylon)
Background: Smoking, a prevalent and detrimental habit, has long been recognized as a major risk factor for various health conditions, including cardiovascular diseases and various cancers. Objectives: This study aimed to examine the impact of smoking on sirtuin 3 (SIRT3), a mitochondrial sirtuin, and selected biochemical variables in individuals with Parkinson’s disease (PD). Materials and Methods: A cross-sectional study was conducted, comprising 100 PD patients and a control group, with both groups further divided into smokers and non-smokers. Blood samples were collected to measure SIRT3 levels and assess various biochemical markers, including oxidative stress, inflammation, and neurotrophic factors. Additionally, disease severity and motor function were evaluated using standardized clinical scales. Results: The results revealed a significant decrease in SIRT3 levels in smokers compared to non-smokers (P ≤ 0.05), suggesting a potential link between smoking and mitochondrial dysfunction in PD. Moreover, biochemical analyzes demonstrated higher levels of oxidative stress markers and pro-inflammatory cytokines in the smoking group, indicating an exacerbation of neuroinflammation and oxidative damage in PD patients who smoke. Interestingly, the study found no significant differences in disease severity and motor function between the two groups. Conclusion: The observed alterations in biochemical variables suggest that smoking may contribute to the dysregulation of essential cellular processes in PD pathogenesis.